Development and evaluation of a school-based physical literacy intervention for children in Germany: protocol of the PLACE study - Carl, Johannes; Schmittwilken, Louisa; Pöppel, Katharina (Frontiers in Sports and Active Living, 2023)
Introduction Fueled by the COVID-19 pandemic, the physical activity behavior of children has reached a concerning level nowadays. By empowering individuals to be physically active throughout the life course, the concept of physical literacy has recently gained increasing attention and adopts a holistic-integrative perspective on PA promotion. Although the field has successively attempted to translate the conceptual ideas of physical literacy into interventions, the theoretical base is heterogeneous and is often lacking within interventions. Furthermore, several countries, including Germany, have not equally adopted the concept yet. Therefore, the goal of the present study protocol is to describe the development and evaluation approach of a PL intervention (“PLACE”) for children in grades three and four within the German all-day schooling system. Methods The physical literacy intervention cultivates explicit theory-content links and comprises 12 heterogeneous sessions (each 60-90 min in length). The study contains three different phases with two initial pilot studies and a subsequent main study. The two pilot studies take a mixed-methods character by drawing on quantitative pre-post-designs as well as interviews with children (in groups). In the main study, we will longitudinally compare the course of PL values (five outcome domains: physical, affective, cognitive, social, behavioral) between two study arms: school classes of children are either assigned to an intervention condition (regular physical education and health care plus PL intervention) or to a control condition (regular physical education and health care only). Discussion The findings of this study will provide evidence on how to structure a multicomponent intervention in Germany based on the PL concept. In summary, the results will report on the effectiveness of the intervention and, therefore, decide whether to scale-up the intervention.